Karakteristik Klinis dan Kesintasan Keratoplasti Tembus Optik di Layanan Tingkat Tersier di Indonesia: Studi Retrospektif 4 Tahun - Syska Widyawati; Tjahjono D. Gondhowiardjo; Rina La Distia Nora; Yulika Harniza; Cut Putri Samira; Ivana Beatrice Alberta (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2022)
Introduction: Purpose, to evaluate patient demographic characteristics, indications and variables related to penetrating keratoplasty (PK) survival. Study design, this study was retrospective case series. Methods: We trace all medical records of PK patients from 2015 to 2018 in Cipto Mangunkusumo Hospital Jakarta. The traced variables were indications of surgery, corneal vascularization, previous failed graft, glaucoma after PK, and other complication. PK survival rate is shown in the Kaplan Meier curve using SPSS v20.0. Results: A total of 214 patients underwent PK (men 67.3%, woman 32,7%) with mean age of 42.11 (0-85) years were included in this study. Three most common indications of keratoplasty were corneal scar (32.7%), infectious corneal ulcer (25.5%), and failed graft (19.2%). The overall graft survival rate for PK is 61.7%. The mean graft survival time was 14.388 ± 0.580 months (95% CI; 13.252-15.524). Conclusion: The graft survival rate for penetrating optic keratoplasty was 61.7%. Establishing an appropriate early diagnosis, reasonable surgical procedures, close monitoring, and early detection of complications with proactive interventions lead to better outcomes. Further research is needed to determine the relationship between the risk factors for corneal graft failure.